Economic study for blend membrane production - A. El-Gendi; H. Abdallah; A. Amin (Bulletin of the National Research Centre, 2021)
Abstract Background In this work, an economic study for production reverse osmosis (RO) membrane from a blend of polyvinylchloride (PVC) with cellulose acetate (CA) was investigated. The model for predicting RO membrane performance was developed based on laboratory experimental data. The economic study was conducted to investigate the feasibility of producing blend RO polyvinylchloride/cellulose acetate (PVC/CA) membrane using a large-scale batch casting machine was developed and fabricated in workshop in the National Research Centre, Egypt. Results The cost of the prepared blend membrane using batch casting machine technique reached to 36 $/m2 for flat sheet polymeric membrane which was cheaper than the cost of sheets of commercial RO membranes. The original capital investment will be recovered in 7.5 years with estimation of machine lifetime 25 years. Conclusions The economic study revealed that the establishing small factories to produce blend membranes using the fabricated machine is a promising and will create a reasonable profit.